In Silico Molecular Docking and ADMET Evaluation of Bioactive Phytochemicals from Urtica dioica (Sisnu) as Potential Anti-Cancer Agents - DHAMI, GOVIND BAHADUR; Bhatt, Madhab Raj; Joshi, Shiv Raj; Joshi, Bhawani Datt (Tribhuvan University Journal, 2026)
This study adopted in silico molecular docking and ADMET approach to investigate the therapeutic potential of bioactive phytochemicals named Quercetin, Scopoletin, and Kaempferol, from Urtica dioica (Sisnu) for anticancer activity against human receptor tyrosine kinase(PDB ID: 4RT7), Janus Kinase (JAK2; PDB ID: 3UGC), and MYC transcription factor (PDB ID: 1NKP). These compounds were chosen because Urtica dioica is traditionally used in anti-inflammatory, anticancer ethnomedicine, and reported bioactivity with a suitable molecular size for oral therapeutics. This study fills the gap by directly comparing their ADMET, toxicity, and docking in the same computational workflow. The physicochemical properties, pharmacokinetics, and drug-likeness properties were assessed by using the SwissADME web tool. ProTox 3.0 was used to predict the acute toxicity of the phytochemicals, and Auto Dock Vina was used to investigate the interactions. All three compounds showed an acceptable physicochemical profile, modest lipophilicity, favorable solubility, and full alignment with the five rules of Lipinski, compatible with efficient oral bioavailability. Scopoletin showed the most balanced ADME profile, while quercetin and kaempferol are better suited for non-CNS targets. Predicted toxicity was manageable for all three phytochemicals, with lower liabilities for scopoletin and kaempferol, though PAINS and Brenk alerts around the catechol motif in quercetin call for careful experimental validation and optimization. Docking showed favorable scores for quercetin and kaempferol against the receptor tyrosine kinase (−9.5 to −9.8 kcalmol⁻¹) and Janus kinase 2 (−9.0 kcalmol⁻¹). These in silico results indicate quercetin and kaempferol merit further investigation as RTK/JAK2 directed anticancer scaffolds, while scopoletin may offer an ADME advantaged chemotype; experimental validation is required before therapeutic claims.